New energy-efficient composite wall from expanded polystyrene concrete in fixed formwork (Advances in Civil and Architectural Engineering, 2025)
This study focused on the development and verification of the effectiveness of a new energy-efficient composite wall made of polystyrene foam concrete in a fixed formwork, prepared using light steel thin-walled structures and polystyrene foam concrete as an aggregate. This research included the development of the new patented solution, a multi-criteria analysis of this solution through comparison with the most common solutions, and experimental investigations of the heat transfer resistance of the new wall. Based on the results of a multi-criteria analysis involving eight criteria, it was established that the new solution of a composite wall in a fixed formwork is more effective than 13 traditional alternatives. Experimental studies on the heat transfer resistance, conducted at the laboratory of the Scientific Research Institute of Building Structures in Kyiv, demonstrated the heat-insulating properties of the new wall. The installation of the new wall at an actual construction site confirmed the reduction in labour and material consumption owing to the new technology. Thus, for the first time, the experimental results of the heat transfer resistance of the new wall at two cross sections (maximum thickness of polystyrene foam concrete and maximum accumulation of steel elements) made it possible to substantiate the need for external insulation of the wall. Low values of the specific labour intensity, material intensity, as well as the possibility of installing wall elements with minimal use of construction equipment make it possible to use the developed solution for a wide range of construction structures.